Rotifers enriched with iodine, copper and manganese had no effect on larval cod (Gadus morhua) growth, mineral status or redox system gene mRNA levels. (22nd November 2013) - Penglase, Sam; Hamre, Kristin; Olsvik, Pål A; Grøtan, Espen; Nordgreen, Andreas
Abstract It currently remains unclear if rotifers contain sufficient mineral levels to meet larval fish requirements. In this study, rotifers were enriched with a commercial enrichment (control), or with additional iodine, iodine and copper, or iodine, copper and manganese, and the effects of feeding these rotifers to Atlantic cod (Gadus morhua) larvae from 3 to 18 days post hatch were investigated. Rotifer enrichment with minerals was successful, but Mn enrichment also increased rotifer zinc levels. No differences were observed between treatments in larval growth or survival, or in the mRNA levels in the majority of the redox system genes analysed. Only Zn levels increased in cod larvae in response to mineral enrichment of rotifers. Apart from Zn, little evidence was found to suggest that cod larvae require increased concentrations above the control rotifer levels of the essential elements studied here.